Characterization of the Gene Encoding S-adenosyl-L-methionine (AdoMet) Synthetase in Penicillium chrysogenum; Role in Secondary Metabolism and Penicillin Production - Domínguez-Santos, Rebeca; Kosalková, Katarina; Sánchez-Orejas, Isabel-Clara; Barreiro, Carlos; Pérez-Pertejo, Yolanda; Reguera, Rosa M.; Balaña-Fouce, Rafael; García-Estrada, Carlos (Microorganisms (Basel), 2021)
The filamentous fungus Penicillium chrysogenum (recently reidentified as Penicillium rubens) is used in the industrial production of the β-lactam antibiotic penicillin. There are several mechanisms regulating the production of this antibiotic, acting both at the genetic and epigenetic levels, the latter including the modification of chromatin by methyltransferases. S-adenosyl-L-methionine (AdoMet) is the main donor of methyl groups for methyltransferases. In addition, it also acts as a donor of aminopropyl groups during the biosynthesis of polyamines. AdoMet is synthesized from L-methionine and ATP by AdoMet-synthetase. In silico analysis of the P. chrysogenum genome revealed the presence of a single gene (Pc16g04380) encoding a putative protein with high similarity to well-known AdoMet-synthetases. Due to the essential nature of this gene, functional analysis was carried out using RNAi-mediated silencing techniques. Knock-down transformants exhibited a decrease in AdoMet, S-adenosyl-L-homocysteine (AdoHcy), spermidine and benzylpenicillin levels, whereas they accumulated a yellow-orange pigment in submerged cultures. On the other hand, overexpression led to reduced levels of benzylpenicillin, thereby suggesting that the AdoMet synthetase, in addition to participate in primary metabolism, also controls secondary metabolism in P. chrysogenum.